2020
DOI: 10.1037/neu0000594
|View full text |Cite
|
Sign up to set email alerts
|

Blast concussion and posttraumatic stress as predictors of postcombat neuropsychological functioning in OEF/OIF/OND veterans.

Abstract: Objectives: Many combat Veterans exhibit cognitive limitations of uncertain origin. In this study, we examined factors that predict cognitive functioning by considering effects of blastrelated concussion (BRC), non-blast-related concussion (NBRC), and posttraumatic stress disorder (PTSD) symptoms. Analyses specifically tested whether: (a) BRC and NBRC were distinct in their prediction of cognitive performance; (b) a dose-response relationship existed between recurrent concussion (BRC and NBRC) and cognitive im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 68 publications
(112 reference statements)
1
20
0
Order By: Relevance
“…In the case of PCL-5 measures, individuals with multiple deployments showed consistently higher scores (median value of 7), which corresponds with greater PTSD symptomatology ( 58 ). Although well-below the threshold for clinical diagnosis (i.e., PCL-5 score ≥ 33), this observation is consistent with a large body of research suggesting a link between multiple deployments, mTBI and increasing vulnerability to developing PTSD and other mental health problems ( 59 , 60 ). These findings should prove useful as researchers work toward developing improved diagnostic tools for distinguishing between the effects of these three conditions that frequently overlap in this population exposed routinely to low-level blast ( 61 , 62 ).…”
Section: Discussionsupporting
confidence: 86%
“…In the case of PCL-5 measures, individuals with multiple deployments showed consistently higher scores (median value of 7), which corresponds with greater PTSD symptomatology ( 58 ). Although well-below the threshold for clinical diagnosis (i.e., PCL-5 score ≥ 33), this observation is consistent with a large body of research suggesting a link between multiple deployments, mTBI and increasing vulnerability to developing PTSD and other mental health problems ( 59 , 60 ). These findings should prove useful as researchers work toward developing improved diagnostic tools for distinguishing between the effects of these three conditions that frequently overlap in this population exposed routinely to low-level blast ( 61 , 62 ).…”
Section: Discussionsupporting
confidence: 86%
“…Military veterans are more likely than civilians to experience head injury associated with blast exposure (i.e., barotrauma) or overpressure associated with discharge of firearms. Some suggest that barotrauma may have unique effects on the brain that could result in characteristically different rates and presentations of headache [ 73 ], though the body of research is equivocal, with some reporting evidence that head injury mechanisms have little differential impact on brain functioning [ 74 ]. Unfortunately, the body of literature describing unique contributions of barotrauma to TBI (and TBI-related headache) is sparse and does not provide enough information to lead to a reasonable stratification of head injury type (i.e., barotrauma versus blunt trauma).…”
Section: Discussionmentioning
confidence: 99%
“…Population based estimates of PTSD in the general community range from 7 to 8% and higher rates (up to approximately 20%) have been reported in American service members returning from deployment 82‐84 Research utilizing a screening measure to examine symptoms of PTSD in patients admitted to the hospital and diagnosed with mTBI described PTSD as a rare comorbidity following their injury (2.8%) 85 . Nelson et al observed a link between PTSD symptoms and concussion in a sample of veterans; yet findings lack generalizability to the general population 86 …”
Section: Expert Opinionmentioning
confidence: 99%